Implementasi Metode LCG Pada Aplikasi CBT Untuk Tes Potensi Akademik Berbasis Web - Rizky Rinaldi (Indonesian Society of Applied Science, 2022)
In the Academic Potential Test of new students at the Raudhatul Akmal Islamic College (STAIRA) Batang Kuis, do not yet have a Computer Based Test (CBT) or a computer-based exam for the freshman academic potential test exam. So that the exam is still carried out manually and costs a lot of money in its implementation. But it also makes the exam process less carried out because some students can cheat when filling in answers by cheating friends. Therefore, in this study aims to create a web-based Computer Based Test (CBT) application and randomize the questions in it by applying the Linear Congruent Generator (LCG) method. The result of this study is a web-based application for academic potential test exams that are expected to overcome the problems that exist in the current STAIRA Batang Kuis. The order of the questions will be automatically randomized when students conduct an academic potential test exam based on their respective student identification numbers.